Experimental investigation on flow condensation of zeotropic mixtures of methane/ethane in a horizontal smooth tube. (January 2018) - Zhuang, X.R.; Chen, G.F.; Guo, H.; Song, Q.L.; Tang, Q.X.; Yang, Z.Q.; Zou, X.; Gong, M.Q.
Highlights: Condensation flow patterns of methane/ethane mixtures were investigated. A new flow pattern transition criteria for zeotropic mixtures was proposed. Condensation heat transfer of methane/ethane mixtures was studied experimentally. An improved heat transfer correlation for different flow patterns was carried out. Abstract: An experimental investigation on condensation flow pattern and heat transfer coefficient of methane/ethane mixtures (0.27/0.73, 0.54/0.46 and 0.7/0.3 by mole) in a horizontal smooth tube with inner diameter of 4 mm was carried out. The tests were conducted at saturation pressure of 1.5–2.5 MPa with mass flux of 98–257 kg m −2  s −1 and heat flux of 15.1–44.4 kW m −2 over the entire vapor quality range. The effects of concentration, saturation pressure, heat flux, mass flux and vapor quality were analyzed and discussed. A new annular/non-annular flow pattern transition criteria on condensation for zeotropic mixtures was carried out. The new transition criteria took the influence of mass transfer resistance into consideration and had satisfactory predictive ability in present study. Moreover, the experimental data were compared with many condensation heat transfer correlations of mixtures. An improved heat transfer correlation for zeotropic mixtures based on flow patterns was proposed. The new correlation combined with the equilibrium method and introduced a new correction factor ( F m ). It achieves better predicting results with a mean absolute relative deviation of 8.02%.